Predictors of COVID-19 vaccine hesitancy in Chad: A cross-sectional study - Takoudjou Dzomo, Guy Rodrigue; Mbario, Edmond; Djarma, Oumaima; Soumbatingar, Ndilbé; Madengar, Mouassede; Djimera, Nadia; Djindimadje, Allarangue; Nguemadjita, Christian; Nassaringar, Guirimadje; Bernales, Margarita; Nangerngar, Togoumbaye; Naissem, Denise; et al. (Frontiers in Public Health, 2023)
Vaccination against the COVID-19 virus is currently the best option to combat the SARS-CoV-2 pandemic worldwide. However, in addition to logistical and economic barriers, hesitancy to be vaccinated threatens to jeopardize efforts to contain the disease. An increasing number of people in Africa are delaying or rejecting recommended vaccines. Since their launch, COVID-19 vaccines have frequently faced rejection worldwide. In this study, we interviewed 5,174 participants from Chad that were representative of the general population, on their perception of COVID-19 vaccines. The survey was conducted from April to May 2021, before the rollout of the COVID-19 vaccination. We found that 47.9% of respondents were willing to receive the COVID-19 vaccine, 29.8% were undecided and 22.3% would not accept the vaccine. We found that urban residents were much more likely to refuse the vaccine than rural residents. We also observed that distrust of COVID-19 vaccines and mistaken beliefs played a crucial role in the reluctance to be vaccinated. Hesitancy to vaccinate against COVID-19 was strongly associated with lack of knowledge, and acceptance of vaccination was primarily associated with fear of the disease. Finally, we identified population profiles among the undecided and the refractors, which will help in developing strategies to combat COVID-19 vaccine resistance.